The Effect of Heat Treatment to the Erosion Rate of Brass Composite - Aminnudin, Aminnudin; Solichin, Solichin (Journal of Mechanical Engineering Science and Technology (JMEST), 2020)
Brass composites can be improved their mechanical properties by the heat treatment process. The improvement of the mechanical properties of this technique is expected to increase the resistance of the composite to erosion that occurs in the environment of flow water. Brass composites used are composites with fly ash 5, 10, 15 and 20%. The heat treatment process was carried out using an electric furnace without protective gas. Composite heat up to 350°C and 400°C for 30 min. and quenching with water. Before and after the erosion test, the weight of the test specimen was weighed with analytical scales. The treatment process affects the tensile strength of brass composites. The heat treatment process of brass composites with 5% fly ash at 350 °C produces the highest tensile strength. Erosion rate testing on brass composites showed the lowest erosion rate occurred on brass composites with 5% fly ash and heat treatment at 350°C.